Pengembangan UMKM Gedang Kriuk melalui Pelabelan dan Pemasaran Digital di Desa Cibitung Wetan, Bogor - Kamandanu, Dimas Fikri; Sarasono, Andanya Chaerunisa; Gultom, Nadine Debora; Tsani, Anissa Nabila; Kustanto, Destian Yogi; Shakila, Dania Putri Primar Tri; Abdiyah, Mutiara; Rivaldo, Napitupulu Yosefino; Hardjomidjojo, Hartrisari (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The MSME Gedang Kriuk in Cibitung Wetan Village processes young papayas into value-added products that is becoming a signature souvenir of Pamijahan. However, the business owners still face marketing limitations and do not yet have proper packaging labels. To address these challenges, an assistance program was carried out focusing on packaging label development and digital marketing through social media. The program aimed to enhance product competitiveness and expand marketing reach beyond the village area. It was conducted from January 4–20, 2025, in Cidamar, Cibitung Wetan Village, Pamijahan, Bogor Regency. Activities began with identifying the problems faced by the business owners. The implemented solutions included creating packaging labels and providing guidance on digital marketing, particularly through the establishment of an Instagram account, @galeri.citanku, as a promotional platform for local MSMEs. Digital marketing efforts involved uploading promotional photos and videos, which successfully increased product reach, as indicated by the number of content views exceeding the account’s follower count. As a result, Gedang Kriuk MSME received several new orders, experienced a higher frequency of purchases, and gained positive consumer responses toward its more attractive packaging design.